A relação força-movimento em um contexto histórico e sob a análise do PNLD - Silva, Bruna Kariny da (2017)
This study aims to answer the following questions: What is the concept of mechanical force taught by physics textbooks? Does this concept follow the Newtonian paradigm? , by means of the analysis of six books approved in the Physics PNLD (acronym for Programa Nacional do Livro Didático, Brazilian governmental program to provide free didactic books) of 2015. The methodology used for data analysis was the content analysis based on Bardin (1977). Therefore, the analysis categories were defined previously, based on a bibliographical revision about the development of the force concept, from Aristotle to Newton. In addition to the scientists already mentioned, Philoponus, Buridan and Descartes also have important contributions to this research. After this analysis, it was possible to conclude that all the verified collections presented configurative elements of Cartesian-Newtonian s category, and only one of them defined the concept of quantity of motion before the force concept, according to the definitions from Newton s Principia. Other significant result was that in most of the collections, examples that discuss the influence of friction force in the body motion were also found. Thus, we believe that this research can contribute significantly to teacher s work in the classroom, providing conscious reflections on the use of this didactic material.